Action of leucine in heart hypertrophy induced by thyroid hormone in rats (Bioscience Journal, 2016)
Leucine is a regulator of protein metabolism in vivo, but there is little information regarding its effect on hyperthyroidism-induced cardiac hypertrophy. This study aimed to verify the action of leucine in heart hypertrophy using an experimental model of hyperthyroidism in rats. A total of 40 Wistar rats were used and allocated randomly into four groups: control (C), hormone (H), leucine (L) and hormone plus leucine (HL). Hyperthyroidism was induced by administering daily by gavage 20 Î¼g of levothyroxine sodium in aqueous suspension per 100 g of body weight, and leucine was supplemented by adding 5% of the amino acid to conventional food. After 28 days, the heart was removed and weighed; the left ventricle was separated along with the interventricular septum and weighed. Histological slides were made from the left ventricle and stained with hematoxylin-eosin to measure the transverse diameter of cardiomyocytes. Two-way analysis of variance (ANOVA) and Tukey post-test were used and significance level set at 5%. There was a significant increase in the absolute heart weight, the left ventricular weight and cardiomyocyte diameter in rats of the H group compared to the other groups. The addition of leucine inhibited heart hypertrophy. Levothyroxine sodium-induced cardiac hypertrophy in Wistar rats is inhibited by leucine.